El rol del número de cédula en el derecho a la identidad - Javier Ribadeneira Sarmiento (Universidad Hemisferios, 2016)
Among the rights enshrined in our Constitution is the right to personal identity, which is also considered a human right and inalienable of every person since birth. Under the guideline of this right, the article presents a comparative analysis between the repealed Civil Registration, Identification and Registration Law (LRegCiv) and the current Organic Law on Identity and Civil Data Management (LOGIDC), and to deepen the normative changes. Despite the novelty of the current legal framework, this article identifies and lists several errors of conception or omission that the new law contains. Also the article highlighted several concepts that lend themselves to confusion. In addition, with the support of a case study, the mistakes that the administration committed and could still commit are exemplified. It is concluded that the new law is not sufficient to guarantee in a reliable way the right to identity due, mainly, to its gaps and lack of definitions. The author presents and explains the main new legal developments in civil registration. The article was written using mainly legal texts, doctrine, papers of recognized writers and for didactic purposes it analyzes a practical case. It is structured as follows: (i) introduction, (ii) the right to identity, (iii) normative developments, (iv) case study, (v) conclusions and recommendations.